The insulin-like growth factor axis and collagen turnover during prednisolone treatment. Issue 5 (November 1994) - Wolthers, O D; Juul, A; Hansen, M; Müller, J; Pedersen, S
Abstract : Serum concentrations of insulin-like growth factor I (IGF-I) and insulin-like growth factor binding protein 3 (IGFBP-3), the carboxyterminal propeptide of type I collagen (PICP), the carboxyterminal pyridinoline crosslinked telopeptide of type I collagen (ICTP), and the aminoterminal propeptide of type III procollagen (PIIINP) were studied in 10 prepubertal children with asthma (mean age 9.0 years). The children were treated with 2.5 and 5.0 mg/day prednisolone in a randomised double blind crossover trial with run in, treatment, and washout periods of two weeks. No statistically significant effects on serum concentrations of IGF-I and IGFBP-3 were found. Dose related reductions of PICP, ICTP, and PIIINP were observed: the mean (SEM) reduction in PICP was 33.4 (26.3) and 68.4 (20.6) micrograms/l, in ICTP 2.5 (0.5) and 2.9 (0.6) micrograms/l, and in PIIINP 2.1 (0.7) and 3.1 (1.8) micrograms/l during the 2.5 and 5.0 mg prednisolone periods respectively. Short term treatment with low daily doses of prednisolone is associated with suppression of serum markers of type I and III collagen turnover in children with asthma. Intermediate and long term effects remain to be studied.